Fourth International Conference on Autonomic Computing (ICAC'07) 2007
DOI: 10.1109/icac.2007.1
|View full text |Cite
|
Sign up to set email alerts
|

A Regression-Based Analytic Model for Dynamic Resource Provisioning of Multi-Tier Applications

Abstract: Abstract-The multi-tier implementation has become the industry standard for developing scalable client-server enterprise applications. Since these applications are performance sensitive, effective models for dynamic resource provisioning and for delivering quality of service to these applications become critical. Workloads in such environments are characterized by client sessions of interdependent requests with changing transaction mix and load over time, making model adaptivity to the observed workload change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
159
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 208 publications
(166 citation statements)
references
References 11 publications
5
159
0
Order By: Relevance
“…We have introduced a statistical regression-based approach for the CPU demand approximation of different transaction in our earlier paper [25], where we evaluated this approach by using a testbed of a multi-tier e-commerce site that simulates the operation of an on-line bookstore, according to the classic TPC-W benchmark [24]. Using the TPC-W benchmark, we demonstrated that the use of linear regression provides promising results.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…We have introduced a statistical regression-based approach for the CPU demand approximation of different transaction in our earlier paper [25], where we evaluated this approach by using a testbed of a multi-tier e-commerce site that simulates the operation of an on-line bookstore, according to the classic TPC-W benchmark [24]. Using the TPC-W benchmark, we demonstrated that the use of linear regression provides promising results.…”
Section: Related Workmentioning
confidence: 99%
“…The OVSD trace profile has the format shown in Table 1. When we first introduced and applied the regression-based technique for evaluating the transaction cost in [25], there were only 14 different transaction types in TPC-W. The analysis of OVSD workload revealed that the real workloads often have a much higher number of transaction types, e.g., OVSD workload operates over 756 different transaction types.…”
Section: Applying Regression To a Production System With Live Workloadmentioning
confidence: 99%
See 3 more Smart Citations